Evaluation of supraspinatus muscle-to-fat infiltration for rotator cuff tear patients using dual-energy computed tomography - Naoki Takatori, MD, PhD; Yoshiyasu Uchiyama, MD, PhD; Takeshi Imai, MD, PhD; Masahiko Watanabe, MD, PhD (JSES International)
Background: This study aimed to assess fatty infiltration of the supraspinatus muscle (Ssp) using dual-energy computed tomography (CT) in patients with rotator cuff tear. Methods: This study examined 44 patients (49 shoulders; 21 men, 23 women; mean age, 69 years) who underwent magnetic resonance imaging (MRI) and dual-energy CT. Three orthopedic surgeons evaluated fatty infiltration of the Ssp using the Goutallier classification of MRI, and three orthopedic surgeons measured attenuation (in Hounsfield units) for the same slice using dual-energy CT. We evaluated the following: 1) interobserver reliability of the Goutallier classification, 2) correlations between intramuscular muscle-to-fat ratio and tear size in the rotator cuff or Goutallier classification, and 3) the spectrum curve of attenuation for each energy level of the Goutallier stage. Results: The κ value for interobserver reliability was 0.721. Significant positive correlations were identified between intramuscular muscle-to-fat ratio and cuff tear size and intramuscular muscle-to-fat ratio and Goutallier classification. Moreover, the Ssp showed no change in attenuation at Goutallier stage 0, but as Goutallier stage increased, attenuation decreased at low energy. Conclusion: We investigated the evaluation of fatty infiltration in Ssp using dual-energy CT in patients with rotator cuff tears. Positive correlations were seen between the Goutallier classification from MRI and rotator cuff intramuscular fat ratio from dual-energy CT. Moreover, changes in attenuation showed that higher Goutallier stages contained more fat. Our data suggest the potential utility of dual-energy CT for evaluating fatty infiltration of rotator cuff muscles.